Environmental Health Risk Factor in the Community Around of Rejo Agung Baru Sugar Factory Madiun - Inta Hestya; Corie Indria Prasasti (Universitas Airlangga, 2015)
Abstract: Emissions of dust particles (baggase and charcoal) into the air by a sugar factory in the production was pollution to the environment that need to be watched. These pollutants materials get into the house through vents or open doors. The purpose of this research was to describe the risk factor of environmental health relation to the amount of risk exposure PM2,5, the community behaviour and home condition. This research is descriptive research with cross sectional design and the number of samples 14 housewife. Data was collected is PM2,5 levels in a room (analyzed with environmental health risk assessment), weight, behavior of respondents and the condition of the house. The results showed there were 3 people respondents at risk of unsafe exposure to PM2,5 weight and concentration by long in the home 24 hours/day and exposure of 350 days/year for 30 years. Risk factors of behavior related to the habit of smoking family members and the use of insect repellent fuel, while environmental factors (condition of the house) was temperature, humidity and the distance of the house from the sugar factory. Concluded that the respondents have a risk of unsafe exposure to PM2,5 was the respondent with a distance of home < 300 meters, have family members who smoke, use insect repellent and fuel temperature and humidity were not eligible. Required increased awareness of family members of the respondents not to smoke in the house, do not use insect repellent and maximize existin ventilation function.Keywords: Environmental Health Risk Assessment, PM2,5, behavior community, home condition, sugar factor